2016
DOI: 10.1111/jors.12251
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relative Deprivation on Return Intentions Among Potential Migrants and Commuters

Abstract: We empirically analyze the impact of relative deprivation on the intended duration of stay of potential cross-border commuters and migrants. A theoretical model lends support to the hypothesis that deprivation affects the intended duration of stay of migrants in a U-shaped fashion, but does not affect potential commuters. Empirical evidence from one of the most densely populated border regions of the EU confirms both these hypotheses. These results are robust over different estimation methods and apply both wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The literature purports that returning home is a viable option for two opposite types of migrants (Borjas & Bratsberg, 1996 ): those who have achieved their migration goals, for instance, in terms of accumulated experience and earnings potential in a foreign labour market, and those who failed to integrate in the labour market for example because they are unemployed (Pecoraro, 2012 ), earn lower wages compared to their reference group (Huber & Nowotny, 2016 ; Stark & Taylor, 1991 ), or face tougher than expected conditions in the host country (Caron & Ichou, 2020 ; Constant & Massey, 2002 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The literature purports that returning home is a viable option for two opposite types of migrants (Borjas & Bratsberg, 1996 ): those who have achieved their migration goals, for instance, in terms of accumulated experience and earnings potential in a foreign labour market, and those who failed to integrate in the labour market for example because they are unemployed (Pecoraro, 2012 ), earn lower wages compared to their reference group (Huber & Nowotny, 2016 ; Stark & Taylor, 1991 ), or face tougher than expected conditions in the host country (Caron & Ichou, 2020 ; Constant & Massey, 2002 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The literature purports that returning home is a viable option for two opposite types of migrants: those who have achieved their migration goals, for instance, in terms of accumulated experience and earnings potential in a foreign labour market (Borjas and Bratsberg 1996), and those who failed to integrate in the labour market (Borjas and Bratsberg 1996) for example because they are unemployed (Pecoraro 2012), earn lower wages compared to their reference group (Stark and Taylor 1991;Huber and Nowotny, 2016), or face tougher than expected conditions in the host country (Constant and Massey 2002;Caron and Ichou 2020).…”
Section: Determinants Of Emigrationmentioning
confidence: 99%
“…53 Studies done by Huber and Nowotny discussed the importance of accepting repatriates' education from their host country to continue their education or find employment in their country of origin after repatriation. 54 Borjas and Brasberg also identified that the least-trained individuals will be the first to return to their homeland, because they believe they do not need much training to get jobs in their country of origin. 55 This study also identified that repatriates who have an economic advantage and know that they can live below their means in their home country also chose to repatriate.…”
Section: Livelihood Developmentmentioning
confidence: 99%